⁠STUDYING AMNIOTIC FLUID INDEX AND LABOR ADMISSION TEST ON TERM HIGH-RISK PREGNANCY AND THEIR ASSOCIATION WITH PERINATAL AND LABOR OUTCOMES - Dr. Pooja; Dr. Madhuri Rathod Anil; Dr. Shruti Varavi (The Bioscan, 2024)
Background: There is substantial literature data concerning role of LAT and AFI in assessing fetal and perinatal outcomes. However, existing literature data is scarce for studies done with combination of both the parameters. Aim: The present study aimed to assess the association of amniotic fluid index and labor admission test on the prevention and prediction of perinatal and labor outcomes in term high-risk pregnancies. Methods: The present study assessed 200 high-risk pregnant females admitted to the labor room in a gestation period of ≥37 weeks in labor. On admission, history was taken for all the subjects followed by general physical examination, P/V and P/A examination to assess labor stage after which subjects were sent for ultrasonography to measure AFI and LAT. The study also assessed neonatal outcomes from the condition at discharge, if the neonate needed NICU admission and APGAR scores. Maternal parameters assessed were the color of the liquor, cesarean delivery indications, maternal complications, and mode of delivery. Results: The study results depicted a statistically significant significance for LAT and AFI with p<0.001. Decreased AFI has a higher association with equivocal and pathological and normal AFI had more of normal CTG with p<0.001. Reduced AFI has a significant association with meconium staining of the liquor, and increased chance of NICU admission of neonate with p<0.001. A similar association was seen in the mode of delivery, NICU admission, APGAR score, and LAT. Conclusions: The present study concludes that the amniotic fluid index and labor admission test are noninvasive and simple tests that can serve as a tool for screening high-risk obstetric females in labor with better-reported accuracy.